The Role of the Ministry of Law and Human Rights in the Field of Intellectual Property Rights - Butar Butar, Edgar Thomas; Simamora, Janpatar (Golden Ratio of Data in Summary, 2025)
Intellectual Property Rights (IPR) is a form of ownership of the results of individual thoughts and creativity that must be legally protected. Although various laws exist to protect IPR, such as the Law on Copyright, Patents, and Trademarks, adequate protection can only be realized if IPR is registered. The Ministry of Law and Human Rights (KemenKumHam) plays an important role in protecting IPR through the Directorate General of Intellectual Property Rights (DJKI) and the Regional Office of the Ministry of Law and Human Rights in each province. This study uses a normative juridical approach to examine the role of the Ministry of Law and Human Rights in protecting IPR, including guidance to the community, receipt of registration applications, implementation of law enforcement, communal intellectual property inventory, and socialization to increase public understanding of IPR. The study results show that the Regional Office of the Ministry of Law and Human Rights has a strategic function in increasing public awareness and understanding and providing the necessary legal protection for IPR owners in Indonesia. More intensive efforts in socialization and education to the public, especially for Micro, Small, and Medium Enterprises (MSMEs), are urgently needed to encourage IPR registration and prevent intellectual property violations.